(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Lead is an environmentally persistent toxin that causes pathologies and induced oxidative stress by reactive oxygen species (ROS) causing reduction of antioxidants and a weakening of defense system of the cell. Objective:To evaluate the occupational lead level and its impact on workers in Batteries Manufacturing Factory / Baghdad. Method:Blood, hair and urine samples were taken from 45 occupational lead exposed workers in Batteries Manufacturing Factory in Baghdad with age ranged (25-63) years during the period from October 2010 to the end of January 2011. Flame and flameless Atomic Absorption spectrophotometer were used in the measurements of blood lead and hair lead concentrations, HPLC was used in the measurement of vitamin E concentration, and ELISA was used for the determination of 8-Hydroxydeoxyguansin concentration. Results:The results in this study showed a high concentration of lead in blood and hair for exposed workers in comparison with the normal corresponding values for the control. The results also showed that there was a significant decrease in ? –Aminolevulinic acid dehydratase activity, a low level of vitamin E in the serum and an increase in the level of 8-Hydroxydeoxyguansin in urine of exposed workers. Conclusion:The correlation between oxidative stress parameters and clinical indices implies that there is a disrupted antioxidant balance which might contribute to lead induced toxicity in erythrocytes. Keywords:Lead exposure, ?–Aminolevulinic acid dehydratase, 8- Hydroxydeoxyguansin, Antioxidants, Lead battery.